Furosemide infusion prevents the requirement of renal replacement therapy after cardiac surgery - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2009)
Objective: Acute kidney injury (AKI) is a devastating complication following cardiac surgery and the ideal management is controversial. This prospective, randomized, open-label and double-blinded study analyzed the renoprotective effects of furosemide infusion and intermittent bolus therapy administered with dopamine infusion in cardiac surgical patients. Methods: Between August 1, 2007 and July 31, 2008, 100 adult patients undergoing elective coronary artery bypass surgery (CABG) surgery with normal renal function (creatinine <1.4 mg/dl) were enrolled in the study. The patients were randomized for the comparison of intermittent (Group 1, n=50, 1 mg-3mg/kg) and continuous infusion of furosemide (Group 2, n=50, 10mg/ml). Continuous variables were expressed as mean +/- SD and compared by unpaired Student's t test or ANOVA for repeated measures. Statistical significance was assumed if p value was <0.05. Results: Renal replacement therapy (RRT) was used in 5% of patients (all in group 1, p=0.028). The 30-day mortality was 5%. Only 2 patients became hemodialysis dependent in group 1. Group 2 patients showed a continuous and higher urine output postoperatively than group 1 (p<0.001). Both groups had significant increase in peak postoperative serum creatinine values (p<0.001), however peak postoperative creatinine-clearance was significantly lower in group 1 (p<0.001). Conclusion: Acute kidney injury necessitating RRT makes a small percentage of patients undergoing cardiac surgery and if RRT is not required the survival is excellent. Continuous infusion of furosemide seems to be effective in promoting diuresis and decreasing the need for RRT However further multicenter studies with different doses of furosemide are required to confirm these results. (Anadolu Kardiyol Derg 2009; 9: 499-504)
Keywords: Acute kidney injury; coronary artery bypass surgery; furosemide; renal replacement therapy; ACUTE KIDNEY INJURY; CARDIOPULMONARY BYPASS; RISK-FACTORS; FAILURE; DOPAMINE; DIALYSIS; DYSFUNCTION